Technological Innovation in Energy Management: A Case Study of Implementation in the Industrial Sector - Rahim, Radiyan; Jamhur, Annisak Izzaty (Jurnal Teknik dan Teknologi Tepat Guna, 2024)
This study explores technological innovations in energy management within the industrial sector through a detailed case study implementation. The research aims to analyze the impact of new technologies on enhancing energy efficiency and sustainability. Methodologically, a comprehensive case study approach is employed to investigate the practical application of these innovations in an industrial setting. The findings highlight significant improvements in energy consumption monitoring and operational efficiency, facilitated by advanced technological solutions. This research contributes valuable insights into the transformative potential of technology in industrial energy management.